Changes in perceptions of mental fatigue during a season in professional under-23 English Premier League soccer players. Issue 4 (1st October 2020) - Abbott, William; Brownlee, Thomas E.; Naughton, Robert J.; Clifford, Tom; Page, Richard; Harper, Liam D.
ABSTRACT: The present study assessed changes in academy soccer players' perception of mental fatigue (MF) across a competitive season, investigating the relationship between MF and other subjective measures of wellness. Ten players completed a modified Brief Assessment of Mood (BAM+) questionnaire that included the question: "How mentally fatigued do you feel"? on match-day (MD) and one (MD+1), two (MD+2) and three (MD+3) days post-match (35 matches). Players reported their MF, along with other subjective measures (sleep, muscle soreness, fatigue and motivation). Results found MF was elevated on MD+1 (43±1 mm) compared to all other days (all P≤0.001). Players reported lower MF on MD+1 in the late-season phase (34±2 mm) compared to both early- (50±2 mm, P≤0.001) and mid-season (46±2 mm, P≤0.001). This coincided with an 80%-win rate in the late-season phase versus the early- (33%) and mid-season (50%). There were very strong repeated-measures correlations between changes in MF and sleep ( r =−0.77), muscle soreness ( r =0.94), fatigue ( r =0.92) and motivation ( r =−0.89; all P ≤ 0.0005). In conclusion, MF was closely aligned to match success and other wellness variables. This data suggests a potential lack of sensitivity for identifying MF using a subjective questionnaire. Therefore, researchers and practitioners could work together to identify other ways of practically assessing MF.